Mullerian Anomaly Presenting as Chronic Pelvic Pain - Wadhwa, L; Nain, S; Jindal, S; Gupta, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://dx.doi.org/10.3126/njog.v9i1.11198 NJOG 2014 Jan-Jun; 2(1):87-88